0

# Remove the brackets from:

Remove the brackets from:
(5x + 3)(x-4)

(2x-1)

thank you very much!

### 1 Answer by Expert Tutors

Vivian L. | Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACHMicrosoft Word/Excel/Outlook, essay comp...
3.0 3.0 (1 lesson ratings) (1)
0
Hi again Kath;
HAPPY THANKSGIVING!
You are like me.  When I was in school, the Holidays were an opportunity to catch-up on homework.  I never learned how to baste a turkey.  Larry is doing all of the cooking today.  I cannot even make the frozen corn.
(5x + 3)(x-4)
First, I would like to correct your English.  These are not brackets.  Brackets are [ and ].  These are parentheses.  We have to resolve two parenthetical equations.
Let's FOIL...
FIRST...(5x)(x)=5x2
OUTER...(5x)(-4)=-20x
INNER...(3)(x)=3x
LAST...(3)(-4)=-12
You may already know that a negative number multiplied by a positive number results in a negative number.
Therefore...
5x2-20x+3x-12
5x2-17x-12

(2x-1)2
This is...
(2x-1)(2x-1)
Let's FOIL...
FIRST...(2x)(2x)=4x2
OUTER...(2x)(-1)=-2x
INNER...(-1)(2x)=-2x
LAST...(-1)(-1)=1
4x2-2x-2x+1
4x2-4x+1